New holistic approach for the management of biofilm‐associated infections by myco‐metabolites. (3rd April 2022) - Ghosh, Sreejita; Nag, Moupriya; Lahiri, Dibyajit; Sarkar, Tanmay; Pati, Siddhartha; Joshi, Sanket; Ray, Rina R.
Abstract: Biofilm‐associated infections have increased excessively over the recent years due to the increased population having impaired immune systems or as a result of certain medical conditions like transplantation, cancer, and any other chronic ailments. The abrupt enhancement of antibiotic resistance and enhanced utilization of biomedical devices offer new opportunities for microbial colonization leading to the development of microbial biofilms. Total eradication of recalcitrant microbial biofilms demands the adoption of a holistic approach and since the fungal metabolites enriched with bioactive compounds show efficacy in inhibiting the multiple factors behind biofilm formation, the anti‐biofilm activities of fungal metabolites need to be appraised. Being effective in preventing various steps of biofilm formation, including inhibition of surface adhesion and cell‐to‐cell communication through quorum quenching, blocking of quorum sensing receptors, and enzymes involved in microbial cell wall biosynthesis, targeting the virulence factors and finally killing of biofilm bound individual cells; myco‐metabolites are found effective as a potent holistic anti‐biofilm agent. The wide spectrum of bioactive substances of fungi and their anti‐biofilm activities against different pathogens and their multitarget characteristics are very promising in the field of treating biofilm infections.